Taxonomic notes on Spiraea martini Léveillé (Rosaceae) - Xu, Dong-Xian; Zhu, Xin-Xin; Liu, Quan-Ru (Phytotaxa, 2017)
Examination of specimens and literature as well as the field survey shows that Spiraea cavalariei Léveillé, S. martini var. pubescens Yu, and S. martini var. tomentosa Yu matches perfectly with Spiraea martini Léveillé, so previous three names are here relegated to the synonymy of Spiraea martini Léveillé.